Bird diversity and conservation in the lower delta of the Paraná River, Argentina - Fracassi, Natalia Gabriela (2021)
The Delta of the Paraná River, one of the most important wetlands in South America, harbors subtropicaland temperate bird species. Although this region is key for biodiversity conservation, aspects such as speciescomposition and conservation status, and their relationship with vegetation types are poorly known. Herewe described bird richness and composition of this area, with emphasis on the relationship between vegetationtype and the presence of key bird species. We compiled systematic studies conducted during the 2007-2020 periodand performed new surveys to elaborate a checklist of bird species and assess completeness. We reviewed a total of 12 studies distributed along five landscape units and nine vegetation types. We recorded 245 species, though the species accumulation curve indicates that the number of species could be even higher for the area. Most species were recorded in freshwater marshes, watercourses and grasslands in Entre Ríos. We identified 14 (5.7%) threatened species (e.g., Spartonoica maluroides, Limnoctites rectirostris and Sporophila palustris), most of them registered in grassland and freshwater marshes. To our best knowledge, the list of species is the most comprehensive one for the area, showing that 23.7% lf all bird species known for Argentina. Our results suggest the importance of freshwater marshes, watercourses and grasslands as key vegetation types for birds.